Analisis Minat Penggunaan Mobile Banking Syariah Pada Generasi Milenial Studi Kasus Mahasiswa Program Studi Perbankan Syariah Semester VIII - Rica Putriana; Junda Harahap; Enni Efrida Nasution (STIKes Ibnu Sina Ajibarang, 2023)
The purpose of this study is to find out: (1) the use of Islamic mobile banking in the Islamic economy, (2) the interest of semester VIII Islamic banking students in using Islamic mobile banking. This research is a field research, namely describing and explaining facts as they are, not adding and not subtracting, which is descriptive in nature and tends to use analysis, describing social problems and research that produces findings that can be obtained by means of observation, interviews, documentation and literature. Data analysis is done by data collection, data reduction, data presentation and verification. The results showed that (1) interest in using sharia mobile banking in Islamic economics is permissible as long as it fulfills sharia principles that there is no usury, maisir, and other activities that are contrary to Islamic ethical principles (2) interest in using sharia mobile banking in semester VIII students of Islamic banking is still low because they do not have full cellphone memory, do not really understand the use of sharia mobile banking, BSI bank which only exists in Sibuhuan and has no branches so it is difficult to reach, and is not too important in the use of sharia mobile banking in everyday life.